2022
DOI: 10.1017/s1478951522000268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virtual reality-based exercise intervention on sleep quality in children with acute lymphoblastic leukemia and healthy siblings: A randomized controlled trial

Abstract: Objective Sleep is one of the important measurements of the quality of life for children especially suffering from a chronic illness such as cancer. Our aim was to determine the changes in sleep quality and to investigate the effect of virtual reality-based exercise (VRBE) approaches on sleep in patients with acute lymphoblastic leukemia (ALL) off treatment. Method The participants (ALL and healthy siblings) were evaluated for sleep quality with polysomnography and “Children's Sleep Habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The population’s age ranged from 3 years to over 70 years. Among all studies, 16% (4/25) reported pediatric cancer patients aged <18 years, who were mainly diagnosed with leukemia, lymphoma, or brain cancer [ 37 , 42 , 50 , 52 ]. The remaining 84% (21/25) of studies reported adults with various cancers, including breast cancer, leukemia, lymphoma, brain cancer, nervous system cancer, lung cancer, gastrointestinal tract cancer, abdominal and pelvic cancer, oropharyngeal cancer, multiple myeloma, colorectal cancer, melanoma, bladder cancer, prostate cancer, pancreatic cancer, and ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population’s age ranged from 3 years to over 70 years. Among all studies, 16% (4/25) reported pediatric cancer patients aged <18 years, who were mainly diagnosed with leukemia, lymphoma, or brain cancer [ 37 , 42 , 50 , 52 ]. The remaining 84% (21/25) of studies reported adults with various cancers, including breast cancer, leukemia, lymphoma, brain cancer, nervous system cancer, lung cancer, gastrointestinal tract cancer, abdominal and pelvic cancer, oropharyngeal cancer, multiple myeloma, colorectal cancer, melanoma, bladder cancer, prostate cancer, pancreatic cancer, and ovarian cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to postmastectomy syndromes, other types of CRDs could also be intervened effectively by VRER. Studies showed that VRER can improve limb function, joint ROM, edema rates, cognition, respiratory disturbance index, apnea, ADLs, and QoL in cases of CRDs like CRCI, CIPN, and cancer-related sleep disorder [ 38 - 40 , 43 - 45 , 48 , 50 - 52 , 54 , 55 ]. The potential mechanism was speculated to be closely related to the virtualization and interaction of VR.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dropouts, 12 studies reported a rate of less than 20%, and 5 studies had 26.2% to 60% dropouts. The dropout rate was reduced by session supervision; supervised interventions had an 11.1% dropout rate [33,[37][38][39][40]46,48,50,54] compared with 25.4% for those without supervision [34,35,41,42,44,47,[51][52][53]. The dropout rate increased with age [41,43,44,46,47,50,52], male gender [50,51], and cancer aggressiveness [44,46,47,52,53].…”
Section: Feasibility and Adherence To Exergaming Interventionsmentioning
confidence: 99%
“…Due to the current technological evolution and children's ability to interact with these devices, recent evidence suggested the use of VR as an effective non-pharmacological intervention in pediatrics, because the inclusion of "gamification" (game elements in educational context) allows children a distraction due to their immersion in virtual play [14,[26][27][28][29][30][31][32]. Actually, VR was tested as an effective method in the management of pain and anxiety of children in oncologic, medical, surgical, and community settings (i.e., during vaccination procedures) [14,23,27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, VR was tested as an effective method in the management of pain and anxiety of children in oncologic, medical, surgical, and community settings (i.e., during vaccination procedures) [14,23,27,30]. The significant impact of VR on supportive care management and quality of life enhancement of pediatric patients with cancer is well established [9,32,33].…”
Section: Introductionmentioning
confidence: 99%